The Image Of Women In Kurdish Television Advertisements - Awat Yakub Othman (QALAAI ZANIST JOURNAL, 2021)
Media distribute images of women, in the form of stereotyping of role models or clichés, which is received and absorbed daily by consumers. The present study focuses mainly on television advertisements (TV adverts). TV adverts have a positive and negative influence on human behaviors. They convey messages, sometimes financed by third parties, and are intended to inform or influence people who receive them. Culture plays an important part of representing the image of women because it necessitates an emphasis on the intertextual nature of advertising messages and their interrelatedness to the broader social and cultural discourses on femininity and gender identities. This paper attempts at analyzing a number of selected Kurdish TV adverts where women are being portrayed. These TV adverts are from different Kurdish TV channels. This paper aims at answering the following questions: How is the image of Kurdish women portrayed in these TV adverts? What role do Kurdish women play in these TV adverts? Do TV adverts convey the reality of women in the Kurdish society both in appearance and in character, or is it a reflection of western TV adverts or a mix of both?